1981
DOI: 10.1111/j.0954-6820.1981.tb11632.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Light Chains of Immunoglobulins in Serum from Patients with Rheumatoid Arthritis, Sarcoidosis, Chronic Infections and Pulmonary Cancer

Abstract: ABSTRACT. Free light chains of immunoglobulins were measured in serum from 181 patients with rheumatoid arthritis (RA), sarcoidosis, pulmonary tuberculosis, pulmonary cancer and chronic bronchitis, i.e. patients with long‐term stimulation of the immune system. Increased concentrations of light chains were found in patients with active sarcoidosis, and the light chain level appeared to be a marker of disease activity in sarcoidosis. The mean (±S.D.) concentration of kappa plus lambda chains in active sarcoidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…A possible explanation for this finding is chronic inflammation, which is well described in patients with diabetes (18,19), because chronic inflammation itself is associated with increased polyclonal FLC (20,21).…”
Section: Discussionmentioning
confidence: 87%
“…A possible explanation for this finding is chronic inflammation, which is well described in patients with diabetes (18,19), because chronic inflammation itself is associated with increased polyclonal FLC (20,21).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, most patients with chronic inflammatory diseases and associated renal impairment have high concentrations of polyclonal FLCs, but with substantially normal k/ ratio. [17][18][19][20] The clinical study of elevated sFLCs in renal impairment are unclear. Reports have suggested that the elevated FLCs lead to reductions in immune function and therefore should be classified as uremic toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Such elevations are very common in a wide variety of inflammatory and infectious diseases, which are not frequently associated with renal impairment (12). Conceptually there are two principal reasons why polyclonal sFLCs could have been associated with progressive renal disease.…”
Section: Polyclonal Gammopathymentioning
confidence: 99%
“…In people with CKD, reticuloendothelial clearance and therefore reticuloendothelial health becomes an important component of sFLC clearance. A further consideration is the presence of coincident inflammation, which will further elevate sFLC concentrations (12,13). Although sFLCs do have an immunomodulatory effect (14), there are no studies to date that have assessed their relationship to clinical outcomes in CKD.…”
Section: Introductionmentioning
confidence: 99%